CHARACTERISTICS OF FISH COMMUNTIES ASSOCIATIONS IN THE WATER OF MALAHING VILLAGE, BONTANG CITY, EAST KALIMANTAN - Atmawati, Yuni Khusnul; Irawan, Aditya; Sari, Lily Inderia (Jurnal Perikanan Unram, 2025)
The important role of seagrass beds as habitat for fish communities, both as nursery ground, feeding ground and shelter. The aim of the research was to determine the association of fish communities in seagrass beds in relation to the characteristics of the seagrass species that make up the seagrass beds. The research was carried out in seagrass beds in the waters of Malahing Village, Bontang City, East Kalimantan from October 2024–February 2025, using a purposive sampling method. Sampling consisted of 2 stations with three repetitions. Fish samples were taken using a trap net and seagrass density using a 50x50cm square frame. The seagrass species found at both stations consisted of E. acoroides and T. hemprichii. The fish species caught consisted of 10 families, 11 genera and 15 species. Fish community association was positively correlated with T. hemprichii density.